2013
DOI: 10.1186/1475-2840-12-86
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and abdominal fat are associated with inflammation, but not with clinical outcomes, in peritoneal dialysis patients

Abstract: BackgroundIn the general population, metabolic syndrome (MetS) is correlated with visceral fat and a risk factor for cardiovascular disease (CVD); however, little is known about the significance of abdominal fat and its association with inflammation and medication use in peritoneal dialysis (PD) patients. We investigated the relationship of visceral fat area (VFA) with C-reactive protein (CRP) levels and medication use in PD patients and followed their clinical outcomes.MethodsIn a prospective study from Febru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 39 publications
(44 reference statements)
2
18
1
1
Order By: Relevance
“…The considerable contribution of obesity in general to chronic inflammation in our cohort is surprising and partly in contrast to previous studies describing abdominal/visceral fat as the primary contributor to chronic inflammation . However, the WHR correlation with visceral fat mass was considerably weaker than with the WHeR or the BMI in a collective of the general population, limiting the usefulness of WHR to assess visceral fat mass .…”
Section: Discussioncontrasting
confidence: 98%
“…The considerable contribution of obesity in general to chronic inflammation in our cohort is surprising and partly in contrast to previous studies describing abdominal/visceral fat as the primary contributor to chronic inflammation . However, the WHR correlation with visceral fat mass was considerably weaker than with the WHeR or the BMI in a collective of the general population, limiting the usefulness of WHR to assess visceral fat mass .…”
Section: Discussioncontrasting
confidence: 98%
“…First, we did not perform other machine-based assessments of visceral adiposity such as computed tomography or dual energy X-ray absorptiometry to validate the role of the VAI in measuring visceral adiposity in HD patients. Second, the annual mortality rate in this study was similar to our previously report [ 26 ] and to another study from Taiwan [ 40 ] in dialysis patients, but lower than reported in Western counties [ 10 ]. Furthermore, 34 patients (6.9%) in this study were censored because they were transferred to other dialysis facilities and were no longer followed up, and therefore the annual mortality rate may have been underestimated and the results of the consequent Cox survival analysis may be inaccurate.…”
Section: Discussionsupporting
confidence: 90%
“…It should be pointed out that atherosclerosis tended to be less prevalent in our PD patients and neither inflammatory markers nor lipid levels were found to be independent risk factors for atherosclerosis, although CRP and fibrinogen levels were higher, serum albumin was lower in PD patients (Table 1) and serum cholesterol and lipoprotein (a) levels were similar to HD patients, a condition reported to be associated with a higher risk of developing atherosclerosis in PD therapy (27,28).…”
Section: Discussionmentioning
confidence: 71%